ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP DI TINJAU DARI SELF-CONCEPT - Melly Susanti; Hana Ismatillah; Puji Nurfauziah; Heris Hendriana (IKIP Siliwangi, 2018)
This study aims to describe the mathematical communication abilities in terms of selft concept of studens of class VIII junior high school 10 Cimahi. This research method is included in this type of research descriptive research is qualitative, describes approach the errors of students in answering questions mathematical communication seen from selft concept. The research in the test to 22 students in the sample in this study is 9 students. The determination of the sampling is done by taking the 3 students that have high self concept, 3 students who have self concept, and 3 student have low self concept. The result of data analysis showed the ability of mathematical communication for students who have hgh self concept that is 2 students showed the test of mathematical communication ability enough and 1 student low. Mathematical communication skills for students who have a moderate self concept that is 2 students showed good mathematical cominication ability test and 1 low students. The ability of mathematical communication for students who have a low selft concept that is 2 student showed less mathematical ability test and 1 students enough.